Recent advances in sustainable and safe marine engine operation with alternative fuels - Karvounis, Panagiotis; Tsoumpris, Charalampos; Boulougouris, Evangelos; Theotokatos, Gerasimos (Frontiers in Mechanical Engineering, 2022)
Pursuing net-zero emission operations in the shipping industry are quintessential for this sector to mitigate the environmental impact caused by hydrocarbon fuel combustion. Significant contributions to this are expected from the substitution of conventional marine fuels by alternative, emission-free fuels with lower emission footprints. This study aims to conduct a comprehensive literature review for delineating the main characteristics of the considered alternative fuels, specifically focusing on hydrogen, methanol, and ammonia, which have recently attracted attention from both industry and academia. This study comparatively assesses the potential of using these fuels in marine engines, and their subsequent performance characteristics as well as the associated environmental benefits. In addition, the required storage conditions, space, as well as the associated costs, are reviewed. Special attention is given to the safety characteristics and requirements for each alternative fuel. The results of this study demonstrate that the environmental benefits gained from alternative fuel use are pronounced only when renewable energy is considerably exploited for their production, whereas the feasibility of each fuel depends on the vessel type used and pertinent storage constraints. Hydrogen, ammonia, and methanol are considered best-fit solutions for small scale shipping, requiring minimal on-board storage. In addition, the need for comparative assessments between diesel and alternative fuels is highlighted and sheds light on marine engines’ operational characteristics. Moreover, using combinations of alternative and diesel fuels is identified as a direction towards decarbonisation of the maritime sector; intensifying the need for optimisation studies on marine engine design and operation. This study concludes with recommendations for future research directions, thus contributing to fuel research concepts that can facilitate the shipboard use of alternative fuels.